PERANCANGAN SISTEM E-KATALOG MOBIL BEKAS PADA SHOWROOM IG MOBILINDO: Perancangan Sistem E-Katalog Mobil Bekas Pada Showroom IG Mobilindo - Sri Handayani; Anisya Sonita; Pedro Ginal Victori Pedro (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Abstract— One of the car showrooms that sell used cars at more affordable prices is in Bengkulu city at the IG Mobilindo showroom which offers various types of used cars that can be purchased by local people. Before carrying out the process of buying and selling used cars, of course, it is necessary to carry out a screening process for the cars desired by consumers, starting with the type of car they want, the brand and specifications regarding the used car that consumers will buy. At this stage the IG Mobilindo showroom is still being carried out directly by sales to help explain the used cars that will be promoted. This often has problems in choosing a car that suits the needs and desires of consumers, because the many variations of types, brands and prices of used cars make consumers less flexible in choosing a used car that suits their wishes. This makes consumers only depend on the selection chosen by the showroom. This also results in the length of time it takes for sales to match consumer desires because cars must be promoted and explained one by one. The purpose of this research is to design and build an e-catalog system as a used car information medium to facilitate consumers and sales in the car selection process. The system development method used is Rapid Application Development (RAD), system design method using Context Diagram, Data Flow Diagram (DFD) and Entity Relation Diagram (ERD) and system testing using alpha testing and Beta testing. The results of system testing on the program show that this program can be used as an auxiliary media to become information material for consumers about used car products being sold.